FUNGSI DAN PERANAN PEREMPUAN HINDU DALAM PELAKSANAAN YADNYA DI BALI - Ni Gusti Ayu Kartika (UHN IGB Sugriwa Denpasar, 2021)
Bali is one of the areas that highly upholds culture, where until now Balinese culture is still firmly rooted in every step of the life of its people. Balinese women have added value that plays an important role in preserving culture, because Balinese women occupy a very strategic position as role models in the implementation of culture. Balinese women have triple roles, namely the role of the family, the role of the economy and the role of religious customs. implementation of the maximum role, both in the family environment, workplace environment, and the general public (social cultural/religious community). The purpose of this study is to describe the function and role of Hindu women in the implementation of yadnya in Bali considering the position of women has a very important role and position in the teachings of Hinduism, even women are the pillars of yadnya who have a role starting from the preparation and implementation of yadnya. because the Hindu community in Bali is so thick with the implementation of religious ceremonies, so that the women should also be skilled in making ceremonial facilities and be tenacious in carrying out yadnya activities. This study uses a qualitative method. This study seeks to reveal the functions and roles of Hindu women in the implementation of yadnya in Bali. The results show that the forms of women's roles in Bali, especially in religious ritual activities, mostly play a role in regulating the overall ritual event. The point is that Balinese women from the beginning and from a long time have prepared ritual activities that will be carried out almost every month that in Bali there are many activities that are religious rituals.